Barriers and facilitators to hepatitis C patient engagement: Interview study with general practitioner champions in England - Avelie Stuart; Carina Hörst; Dolores Mullen; Catherine Lowndes; Ruth Simmons; Aneesha Noonan; Monica Desai (PLoS ONE, 2026)
There are people living with a previously diagnosed chronic hepatitis C infection who have been lost to follow up, and people who may have undiagnosed hepatitis C. General Practitioners (GPs) could help to support these patients into care, via offering testing, referring to secondary care, and facilitating prescribing. We conducted semi-structured interviews with 14 GPs, most of whom work with local Operational Delivery Networks (ODNs) with funding from the NHS England Viral Hepatitis Programme as hepatitis C GP Champions. A thematic analysis with a multi-level model (system, provider-levels) and the COM-B (capability, opportunity, motivation: behaviour) framework were used to identify barriers and facilitators to patient identification and (re)engagement. System-level barriers included a lack of hepatitis C incentives for GPs, pressures facing primary care, challenges searching patient records, and a perception that better processes are needed to re-engage patients lost to follow up. GP Champions expressed challenges coordinating regional patient (re)engagement strategies, but also reported successful collaborations with ODNs, other services, and outreach/community partners. Provider-level barriers for all GPs included lack of knowledge of hepatitis C and difficulty managing patient conversations (capability); and lack of GP capacity and difficulty contacting patients (opportunity). Provider-level facilitators included that primary care is holistic and accessible to patients (opportunity), and GP Champions reported how their roles have granted workload capacity and the support of other GPs/healthcare professionals (opportunity) and increased their feelings of personal reward (motivation). Interviewees’ reflections on shared care and their suggestions for the future of hepatitis C care are also presented. This study demonstrates numerous benefits to employing GP Champions to find and offer testing to patients, however system-level barriers are notably persistent. Interviewees said there is further need to address patients holistically, and joint efforts between services/sectors were suggested as means to overcome system and provider level barriers.